Effects of N-Acetylcysteine on FAS Gene Expression Level in Testicular Tissue of Acrylamide-Treated Adult Rats - Elham Shahrzad; Mehrdad Shariati; Sirous Naeimi; Mohammad Amin Edalatmanesh (Fasa University of Medical Sciences, 2021)
Background & Objectives: Acrylamide (ACR) is a chemical with toxic effects on various body tissues. The present study was conducted to investigate the antioxidant effect of N-acetylcysteine (NAC) on the level of testicular apoptosis in acrylamide-treated adult rats. Material & Methods: Thirty-six adult male Wistar rats were randomly divided into 6 equal groups. The intact control group was without treatment, the positive control group (PC) received 50 mg/kg ACR by oral gavage, the negative control group (NC) received 40 mg/kg NAC intraperitoneally, the animals in experimental groups of 1 (EXP1), 2 (EXP2) and 3 (EXP3) received 10, 20 and 40 mg/kg NAC intraperitoneally, respectively, and then all groups received 50 mg/kg acrylamide by oral gavage. The treatment period in all groups was 28 days. At the end of the study, FAS mRNA expression level was measured by real-time PCR and testicular tissue was evaluated histopathologically. Results: The PC group showed a significant increase in FAS gene expression level (p<0.05) and spermatogenic degradation compared to the intact control and NC groups. The EXP1 and EXP2 groups showed decrease in FAS gene expression level (p˃0.05) and spermatogenesis improvement in a dose-dependent manner while the EXP3 group exhibited a significant decrease in FAS gene expression level (p˂0.05) and complete spermatogenesis recovery compared to the PC group. Conclusion: The findings indicate that ACR increases apoptosis and destroys spermatogenesis by increasing FAS gene expression levels. In contrast, at the maximum dose (40 mg/kg), NAC could inhibit ACR-induced apoptosis by reducing FAS gene expression and improves spermatogenesis in rats.